2015
DOI: 10.1111/boj.12341
|View full text |Cite
|
Sign up to set email alerts
|

Rhytidium rugosum(Bryophyta) colonized Scandinavia from at least two glacial refugial source populations

Abstract: The Scandinavian post-glacial history of the moss Rhytidium rugosum is traced on the basis of information from the nuclear markers ITS and gpd for 229 Scandinavian and 81 other specimens. Some haplotypes, groups or lineages identified in a NeighborNet split network are predominantly northern Scandinavian, whereas others are southern. With the distributions of individual haplotypes and the timing of the deglaciation in different parts of Scandinavia, this implies colonization from the south and from the north o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 73 publications
0
25
0
Order By: Relevance
“…in the Alps to see whether its intraspecific geographical variation is consistent with what was hypothesized above for spore-dispersed plants and to possibly trace its post-glacial origin. In Rhytidium, the variation in the nuclear internal transcribed spacers 1 and 2 (ITS) and a portion of the gene region for glyceraldehyde 3-phosphate dehydrogenase (gpd) are considerable and shows a geographic pattern largely consistent with what is known about the late-to post-glacial history of Scandinavia (Hedenäs 2014(Hedenäs , 2015. Compared with Scandinavian regions, Hedenäs (2014) found a high haplotype diversity in a Rhytidium population in Val Poschiavo in SE Switzerland.…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…in the Alps to see whether its intraspecific geographical variation is consistent with what was hypothesized above for spore-dispersed plants and to possibly trace its post-glacial origin. In Rhytidium, the variation in the nuclear internal transcribed spacers 1 and 2 (ITS) and a portion of the gene region for glyceraldehyde 3-phosphate dehydrogenase (gpd) are considerable and shows a geographic pattern largely consistent with what is known about the late-to post-glacial history of Scandinavia (Hedenäs 2014(Hedenäs , 2015. Compared with Scandinavian regions, Hedenäs (2014) found a high haplotype diversity in a Rhytidium population in Val Poschiavo in SE Switzerland.…”
Section: Introductionmentioning
confidence: 85%
“…It was suggested that the more complicated patterns of glacial refugia in and close to the Alps (Schönswetter et al 2005) than in the almost completely ice-covered Scandinavia (Lambeck et al 2010;Westergaard et al 2011;Vorren et al 2013) during the Late Glacial Maximum (LGM, c. 30-16 kA BP) could explain this high diversity. Some European Rhytidium haplotypes that are unique to the Alps were found by Hedenäs (2015). However, such geographically restricted haplotypes were not more common in central Europe than in Scandinavia, as would have been expected if a larger proportion of the species' total diversity had survived in the southern refugia than in the north (cf., Koch et al 2006;Schönswetter et al 2003).…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations